2022
DOI: 10.1038/s41419-022-05222-9
|View full text |Cite
|
Sign up to set email alerts
|

E2F1/CKS2/PTEN signaling axis regulates malignant phenotypes in pediatric retinoblastoma

Abstract: Retinoblastoma (RB) is the most common pediatric intraocular malignancy and is a serious vision- and life-threatening disease. The biallelic mutation of the retinoblastoma gene RB1 is the initial event in the malignant transformation of RB, but the exact molecular mechanism is still unclear. E2F transcription factors can be activated by RB1 loss of function and lead to uncontrolled cell division. Among E2F family numbers, E2F1 has higher expression abundance than E2F2 and E2F3 in RB clinical samples. By integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…TRRUST analysis 23 and WB results indicated that METTL3 interference had a direct impact on the RB‐E2Fs complex, rather than affecting the p53‐p21‐RB‐E2Fs signaling pathway. It is commonly known that when RB is hypophosphorylated, it binds to E2Fs transcription factor dimers and represses the transcription activities of E2Fs 41,42 . Our results suggested that loss of METTL3 function resulted in the suppression of E2Fs, which is achieved by diminishing the p‐RB in goat granulosa cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…TRRUST analysis 23 and WB results indicated that METTL3 interference had a direct impact on the RB‐E2Fs complex, rather than affecting the p53‐p21‐RB‐E2Fs signaling pathway. It is commonly known that when RB is hypophosphorylated, it binds to E2Fs transcription factor dimers and represses the transcription activities of E2Fs 41,42 . Our results suggested that loss of METTL3 function resulted in the suppression of E2Fs, which is achieved by diminishing the p‐RB in goat granulosa cells.…”
Section: Discussionmentioning
confidence: 59%
“…It is commonly known that when RB is hypophosphorylated, it binds to E2Fs transcription factor dimers and represses the transcription activities of E2Fs. 41,42 Our results suggested that loss of METTL3 function resulted in the suppression of E2Fs, which is achieved by diminishing the p-RB in goat granulosa cells. Among the RB-E2Fs target genes, many code for key cell cycle regulators such as AURKB, 43 and we also found that E2F1 inhibition downregulated the expression of AURKB in goat granulosa cells.…”
Section: Discussionmentioning
confidence: 68%
“…Our study incorporated data from TCGA and revealed that only CKS2+ iCAFs exhibited significant prognostic relevance ( P <0.05). CKS2 protein binds to the catalytic subunit of cyclin-dependent kinases, thereby activating their biological functions [ 41 , 42 ]. Gene Ontology (GO) annotations associated with CKS2 include cyclin-dependent protein serine/threonine kinase regulator activity.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 activates transcription and is essential for regulating the cell cycle, apoptosis, and proliferation by targeting DNA promoters [39]. E2F1 has recently been implicated in numerous tumor types, including breast cancer [40] and retinoblastoma [41]. Interleukin-6 (IL-6) is remarkably active in immunity, in ammation, and metabolism [42].…”
Section: Discussionmentioning
confidence: 99%